Apoptotic germ cells regulate Sertoli cell lipid storage and fatty acid oxidation. Issue 6 (December 2018) - Regueira, Mariana; Gorga, Agostina; Rindone, Gustavo Marcelo; Pellizzari, Eliana Herminia; Cigorraga, Selva Beatriz; Galardo, María Noel; Riera, María Fernanda; Meroni, Silvina Beatriz
Abstract : The presence of lipid droplets (LD) and the utilization of fatty acids (FA) as a source of energy are Sertoli cell (SC) putative characteristics. It is well known that SCs can phagocyte and degrade apoptotic germ cells (AGC) resulting in increasing lipid content and ATP levels. A relationship between the regulation of lipid storage and of lipid oxidation in SC might be envisaged. The aim of this study was to analyze whether AGC and FA are able to simultaneously regulate molecular mechanisms involved in lipid storage and in FA oxidation in SC. The experimental model utilized in this study consisted in SC cultures obtained from 20-day-old rats that were co-cultured with AGC or treated with palmitic acid (PA, 500 μM) for 24 and 48 h. AGC and PA increase LD, triacylglycerol (TAG) content and mRNA levels of Plin1, Plin2, Plin3 (proteins involved in TAG storage). Simultaneously, AGC and PA rise the extent of FA oxidation and mRNA levels of Cpt1 and Lcad (proteins involved in FA degradation). Results also show that peroxisome proliferator-activated receptor (PPAR) transcriptional activity, transcription factor which participate in lipid metabolism regulation, increases by AGC and PA treatment in SC. Additionally, the presence of a PPARg antagonist decreases the upregulation of LD content and Plin1 expression. Similarly, the presence of a PPARb/d antagonist reduces the increase in FA oxidation and Cpt1 mRNA levels. Altogether these results suggest that AGC and FA, which probably generate PPAR ligands, regulate lipid storage and fatty acid utilization, contributing to the energy homeostasis in the seminiferous tubules.